Lip balm formulation of onion dayak extract (Eleutherine palmifolia L.) and rosella flowers (Hibiscus sabdariffa Linn.) as a antioxidant and lip color - Lestariningsih, Nanik; Ayatusa’adah, Ayatusa’adah; Maharani, Septia Puteri (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Plant extract contains active compounds beneficial for ultraviolet protection and skin health. No previous studies have formulated lip balm using Dayak onion and rosella flowers. The research aims to gain information on the best lipbalm formulation with parameters from panelists and preparation evaluation (pH test, homogeneity test, stability, smear test, and hedonic test). Experimental research method with completely randomized design (CRD), to identify the significant differences in the lip balm preparations using one-way ANOVA. Lip balm is formulated from an extract of dayak onion (0%,1%,3%,5%,7%) and rosella flower (0%,1%,3%,6%,9%) as a natural moisturizer and natural dye. The dayak onion bulbs and rosella flowers are extracted and tested for phytochemicals and DPPH antioxidants. The research results indicate that the extract of the dayak onion bulbs and rosella flowers are positive containing flavonoid, alkaloid, tannin, and triterpenoid compounds. The dayak onion bulbs have an IC50 value of 1,4366 ppm, whereas the IC50 for rosella flowers is 19,2135 ppm. The lipbalm preparation of F1, F2, F3, and F4 meet the requirements for pH testing, homogeneity test, smear test, and stability test. The results of the hedonic test on 35 panelists indicate that the most preferred color is in F3, texture in F1 and F3, and aroma in F1. The results of the one-way ANOVA test with a confidence level of 95% have a significance of 0,000 indicating a significant difference (P<0,05). The best extract formulation from dayak onion bulbs and rosella flowers in the lip balm innovative cosmetic herbal ingredients was in Formula 1 with extract concentration 1:1 and the best results of the color parameters according to the panelists were at F3.